2015
DOI: 10.1371/journal.pone.0135079
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Health in Diabetes Patients: An Observational Study in Six European Countries in an Era of Austerity

Abstract: IntroductionSupport from individual social networks, community organizations and neighborhoods is associated with better self-management and health outcomes. This international study examined the relative impact of different types of support on health and health-related behaviors in patients with type 2 diabetes.MethodsObservational study (using interviews and questionnaires) in a sample of 1,692 type 2 diabetes patients with 5,433 connections from Bulgaria, Greece, Netherlands, Norway, Spain, and the United K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 34 publications
3
68
0
4
Order By: Relevance
“…Social support is increasingly perceived to be cornerstone in diabetes management (Koetsenruijter et al, 2016(Koetsenruijter et al, , 2015Stopford, Winkley, & Ismail, 2013). Studies have shown that lack of social support is associated with higher levels of HbA1c and diabetes distress (Baek, Tanenbaum, & Gonzarlez, 2014;Mayberry, Egede, Wagner, & Osborn, 2015;Stopford et al, 2013).…”
Section: Self-management and Hardly Reached Peoplementioning
confidence: 99%
See 2 more Smart Citations
“…Social support is increasingly perceived to be cornerstone in diabetes management (Koetsenruijter et al, 2016(Koetsenruijter et al, , 2015Stopford, Winkley, & Ismail, 2013). Studies have shown that lack of social support is associated with higher levels of HbA1c and diabetes distress (Baek, Tanenbaum, & Gonzarlez, 2014;Mayberry, Egede, Wagner, & Osborn, 2015;Stopford et al, 2013).…”
Section: Self-management and Hardly Reached Peoplementioning
confidence: 99%
“…Informal support comes from friends, family and close colleagues and formal support from health professionals, community organisations and local neighbourhoods (Koetsenruijter et al, 2015).…”
Section: Social Support-conceptual Clarificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of network members in illness management forms an aspect of a collective network process, effort and change placing emphasis on collective agency rather than individual self‐efficacy. Recent findings highlight how social involvement with a diverse range of people, activities and groups provides social and psychological opportunities and resources which contribute to self‐management support (SMS) and physical and mental well‐being (Koetsenruijter et al, ; Reeves et al, ). This more recent focus has highlighted a need to better understand how people engage with social capital, support and resources in a way that is acceptable and meaningful to them and members of their networks when managing and living with a long‐term condition.…”
Section: Introductionmentioning
confidence: 99%
“…People's efforts to maintain DRSCA are often implemented in a social context and in interaction with family and social environment (Rintala, Jaatinen, Paavilainen, & Astedt‐Kurki, ). For people with chronic diseases, social support has been defined as assistance from family, friends, neighbours or community organizations (Koetsenruijter et al, ), comprising an important environmental support resource. Therefore, understanding how it relates to DRSCA has crucial implications for health policy and practice (Miller & Dimatteo, ).…”
Section: Introductionmentioning
confidence: 99%